2007
DOI: 10.1007/s00586-007-0375-1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pre-vertebroplasty tumor ablation using laser-induced thermotherapy on biomechanical stability and cement fill in the metastatic spine

Abstract: A biomechanical study comparing simulated lytic vertebral metastases treated with laser-induced thermotherapy (LITT) and vertebroplasty versus vertebroplasty alone. To investigate the effect of tumor ablation using LITT prior to vertebroplasty on biomechanical stability and cement fill patterns in a standardized model of spinal metastatic disease. Vertebroplasty in the metastatic spine is aimed at reducing pain, but is associated with risk of cement extravasation in up to 10%. Six pairs of fresh-frozen cadaver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 33 publications
3
31
0
Order By: Relevance
“…25 Cavity creation in the vertebral body was performed with Coblation Wands (Fig 2), as previously reported by other authors, 19,26,27 in 59/70 levels. The decision not to use Coblation was made intraprocedurally when the advancement of the trocar cannulas through the lytic area did not reveal typical softtissue consistency, but rather fluid consistency, such as in markedly necrotic tumors or in some multiple myeloma lesions.…”
Section: Cavity Creationmentioning
confidence: 99%
“…25 Cavity creation in the vertebral body was performed with Coblation Wands (Fig 2), as previously reported by other authors, 19,26,27 in 59/70 levels. The decision not to use Coblation was made intraprocedurally when the advancement of the trocar cannulas through the lytic area did not reveal typical softtissue consistency, but rather fluid consistency, such as in markedly necrotic tumors or in some multiple myeloma lesions.…”
Section: Cavity Creationmentioning
confidence: 99%
“…The chosen flow rate was similar to that reported in previous cadaveric studies [30,31] and falls within the range reported during clinical percutaneous vertebroplasty (PV) which is 1.2 to 12.0 mL/min [32]. However, in clinical PV intermittent injections are typically performed with pauses due to changing of syringes and/or the needle position, which is often retracted backwards due to excessive pressurization [32].…”
Section: Discussionmentioning
confidence: 60%
“…The following year, Ahn et al 33 confirmed the FEA model of Tshirchart et al 32 in cadaveric tissue. Using laser-induced thermotherapy (LITT) to ablate the tumor immediately before vertebroplasty-facilitated bone cement placement improved biomechanical stability and reduced the risk of cement extravasation over using the vertebroplasty procedure alone.…”
Section: Tumor Debulking Combined With Vertebral Body Augmentationmentioning
confidence: 77%